When to Return to Normal? Temporal Dynamics of Vigilance in Four Situations - Claudia Mettke-Hofmann (Birds, 2022)
Vigilance is an important behaviour to monitor the environment from detecting predators to tracking conspecifics. However, little is known about how vigilance changes over time either without disturbance (vigilance decrement) or after a change occurred. The time course of vigilance can indicate how animals perceive a situation and the potential mechanism used to deal with it. I investigated the time course of vigilance in Gouldian Finches in four situations (familiar environment, two changed environments–novel object at a neutral location (exploration trial) or above the feeder (neophobia trial), novel environment). The frequency of head movements was assessed in four consecutive 15-min blocks in same sex pairs with a high frequency generally seen as indicative of high vigilance. Vigilance decreased over time in the familiar situation indicating vigilance decrement with a similar time course in the exploration trial. Vigilance was consistently high in the neophobia trial and only returned to normal in the last block. Finally, vigilance plummeted in the novel environment and did not return to normal within an hour. Results suggest that perceived threats affected vigilance and that information gathering reduced uncertainty allowing vigilance to return to normal levels but with different time courses depending on the situation.